(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The growing of pineapples is an important part of Kerala, India’s agricultural economy. To optimize agricultural techniques and guarantee sustained crop production, knowing the historical trends and patterns of pineapple planting is crucial. Time series data regarding pineapple planting frequency in Kerala was analyzed using the Autoregressive Integrated Moving Average (ARIMA) and Seasonal Autoregressive Integrated Moving Average (SARIMA) models. In order to better assist farmers and policymakers, we conducted an investigation to determine seasonal fluctuations, trends, and prospective forecasting skills. We hoped that by using these models, we could shed light on the cyclical nature of pineapple planting and help farmers in the region develop more efficient crop management practices, thereby increasing agricultural output.